2005
DOI: 10.1152/ajplung.00066.2004
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB activation and sustained IL-8 gene expression in primary cultures of cystic fibrosis airway epithelial cells stimulated withPseudomonas aeruginosa

Abstract: The progression of lung disease in cystic fibrosis (CF) is characterized by an exuberant inflammatory response mounted by the respiratory epithelium that is further exacerbated by bacterial infection. Recent studies have demonstrated upregulation of nuclear factor-kappaB (NF-kappaB) in response to infection in genetically modified cell culture models, which is associated with expression of interleukin (IL)-8. Using human airway epithelial cells grown in primary culture, we examined in vitro activation of NF-ka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
80
3

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(91 citation statements)
references
References 48 publications
(77 reference statements)
8
80
3
Order By: Relevance
“…The latter observation can be explained at least in part by the ability of Pseudomonas-derived elastase to cleave IL-18 and also by greater numbers of neutrophils and, by corollary, greater levels of NE entering the microbe-infected CF lung. In addition, it has previously been shown that IL-8 expression is prolonged post P. aeruginosa stimulation (40), thus contributing to excessive neutrophil recruitment and NE burden within the CF airways. In support of our findings, NE inhibitors (A1AT, SLPI, elafin, and CMK) were able to inhibit the cleavage of IL-18, and purified NE was shown to rapidly cleave IL-18 in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…The latter observation can be explained at least in part by the ability of Pseudomonas-derived elastase to cleave IL-18 and also by greater numbers of neutrophils and, by corollary, greater levels of NE entering the microbe-infected CF lung. In addition, it has previously been shown that IL-8 expression is prolonged post P. aeruginosa stimulation (40), thus contributing to excessive neutrophil recruitment and NE burden within the CF airways. In support of our findings, NE inhibitors (A1AT, SLPI, elafin, and CMK) were able to inhibit the cleavage of IL-18, and purified NE was shown to rapidly cleave IL-18 in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported higher constitutive expression and increased activation of NF-KB in unstimulated CF airway epithelial cells compared with non-CF cells (25)(26)(27)(28). NF-KB has been shown to exert an anti-apoptotic effect in many cell lines including respiratory epithelial cells (29)(30).…”
Section: Effect Ofssp On Nf-kb Activationmentioning
confidence: 99%
“…Joseph and colleagues demonstrated that in vitro activation of NF-κB in human airway epithelial cells isolated from CF (DeltaF508/DeltaF508) and non-CF (NCF) patients when infected by Pseudomonas aeruginosa elevated nuclear levels of IkB in CF cells, although this increase was transient. They also showed increased baseline translocation of NF-κB to nuclei in primary CF epithelial cell cultures; following Pseudomonas aeruginosa infection, activation of IκB might suppress that of NF-κB [84].…”
Section: Cystic Fibrosismentioning
confidence: 92%